Comparison of nebulised magnesium sulphate and salbutamol combined with salbutamol alone in the treatment of acute bronchial asthma: a randomised study. Issue 5 (20th April 2006) - Aggarwal, P; Sharad, S; Handa, R; Dwiwedi, S N; Irshad, M
Abstract : Objective: To test the hypothesis that combined administration of multiple doses of nebulised salbutamol and magnesium sulphate provides additional benefit compared with salbutamol alone in adult patients with acute asthma. Design: Randomised, double blind, prospective study. Methods: A total of 100 patients presenting to an emergency department with an acute attack of bronchial asthma were randomised to two groups: nebulisation with a combination of salbutamol and magnesium sulphate (group A) and nebulisation with salbutamol only (group B). Both groups received nebulisation thrice at intervals of 20 minutes. Salbutamol and magnesium sulphate were administered in doses of 0.5 mg and 500 mg, respectively, and the solutions were made isotonic to plasma osmolality. Pulse rate, blood pressure, and peak expiratory flow rate (PEFR) were measured at baseline and at 15, 60, 75, and 120 minutes. Serum magnesium levels and blood gases were measured at 0 and 120 minutes in both groups. Results: All patients had either acute severe or life threatening asthma. The baseline characteristics were comparable in the two groups. Both groups showed significant rise in PEFR at all time intervals, however, there was no significant difference between the groups in rise in PEFR at any time point. Serum magnesium levels remained within normal limits, and there was no difference in requirement of additional medication during the study or hospital admission rates in both groups. No significant side effects were noted. Conclusion: This study suggests that there is no therapeutic benefit of adding magnesium sulphate to salbutamol nebulisation in the treatment of patients with acute severe or life threatening asthma.